Analisis Keterampilan Proses Sains Siswa Pada Pembelajaran Berbasis Praktikum - Novita Vandrianur; Hendro Prasetyono (Institute of Advanced Knowledge and Science, 2026)
Science learning does not only emphasize conceptual understanding but also the development of science process skills as an essential competency in the 21st century. Laboratory-based learning is one of the effective approaches to foster these skills through direct observation and experimentation activities. This study aims to analyze Junior High School students’ science process skills in science learning through laboratory-based activities. This research employed a qualitative approach with a descriptive method. The participants were junior high school students engaged in science practicum activities. Data were collected through observation using a science process skills observation sheet covering observing, classifying, interpreting, reasoning, communicating, and asking questions. The data were analyzed descriptively to identify the emergence of each skill during the practicum process. The results revealed that observing, communicating, and asking questions skills were well developed, while interpreting, reasoning, and classifying skills were not yet optimally achieved. Therefore, more structured practicum design and intensive teacher guidance are required to enhance all aspects of science process skills.